Neuropsychological outcome after unilateral pallidotomy for the treatment of Parkinson's disease. Issue 3 (1st September 2000) - Rettig, Gayle M; York, Michele K; Lai, Eugene C; Jankovic, Joseph; Krauss, Joachim K; Grossman, Robert G; Levin, Harvey S
Abstract : OBJECTIVE: To assess the long term cognitive outcome of unilateral posteroventral pallidotomy (PVP) and the overall efficacy of the surgery. METHODS: Forty two (29 left and 13 right PVP) patients with Parkinson's disease underwent neurological and neuropsychological testing before PVP and at 3 and 12 months after PVP. The neuropsychological testing battery emphasised measures of verbal learning and memory, visuospatial abilities, speed of information processing, executive functioning, and affective functioning. RESULTS: All patients demonstrated motor improvements after surgery during their off state, and 86% of patients also showed improvements in motor functioning in their on state. Repeated measures ANOVA showed significant improvements in confrontational naming, visuospatial organisation, and affective functioning 3 months and 12 months after surgery, with inconsistent improvements in executive functioning 12 months post-PVP. Patients demonstrated a transient impairment in verbal memory, with verbal learning performance returning to baseline 12 months post-PVP after a significant decline 3 months after PVP. When three patients with lesions extending outside of the PVP were excluded from the analysis, a decline in verbal fluency performance after PVP was not found to be significant. Differences due to side of lesion placement were not found on any of the cognitive measures. CONCLUSIONS: In the largest long term follow up study reported to date, the cognitive changes found up to a year after PVP are minimal compared with the robust improvements in motor function. The findings highlight the need to investigate the relation between the specific fibre tracts affected by the lesions and cognitive outcome.